2018
DOI: 10.20996/1819-6446-2018-14-5-654-663
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pre-Diabetes on the Rate of Major Adverse Cardiovascular Events in Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Цель. Оценить связь предиабета с неблагоприятным прогнозом у пациентов с ишемической болезнью сердца (ИБС), перенесших коронарное шунтирование (КШ). Материал и методы. Проведено наблюдение 347 пациентов с ИБС, подвергшихся КШ в 2006-2009 гг. Пациенты разделены на 3 группы: 148 пациентов с сахарным диабетом (СД) 2 типа (медиана возраста 58 лет, медиана срока отдаленного наблюдения-1,8 года), 23 пациента с предиабетом-нарушение гликемии натощак, нарушение толерантности к глюкозе или их сочетание (медиана возраст… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Since the presence of concomitant DM not only affects the choice of the myocardial revascularization strategy [4,5], but also the prognosis after such interventions [6], attention is now being paid not only to the presence of DM, but also to the degree of glycemic control [7][8][9]. In addition, since even the presence of prediabetes can affect the prognosis in cardiac patients [10], active screening of early carbohydrate metabolism disorders before coronary interventions is justified [11][12][13]. Moreover, some researchers go further, evaluating the indexes of insulin resistance in patients before cardiac surgery [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Since the presence of concomitant DM not only affects the choice of the myocardial revascularization strategy [4,5], but also the prognosis after such interventions [6], attention is now being paid not only to the presence of DM, but also to the degree of glycemic control [7][8][9]. In addition, since even the presence of prediabetes can affect the prognosis in cardiac patients [10], active screening of early carbohydrate metabolism disorders before coronary interventions is justified [11][12][13]. Moreover, some researchers go further, evaluating the indexes of insulin resistance in patients before cardiac surgery [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a trend of an increased number of performed CABG compared to PCI was noted in some centers [ 6 ], as well as increased attempts to identify previously undiagnosed diabetes mellitus or prediabetes before CABG surgery. Several studies have shown that disorders of carbohydrate metabolism negatively affected the results of myocardial revascularization [ 7 , 8 , 9 , 10 ]. However, some data could not support these statements, in particular, Djupsjo C. et al did not reveal an effect of newly diagnosed diabetes and previously known pre-diabetes on the long-term survival in patients who underwent CABG [ 11 ].…”
Section: Introductionmentioning
confidence: 99%